Impact of Quality and Self-Care on The Acceptance of Safety Glasses in an Organization - Bazán Deza, Roger Gonzalo (2023)
The problem presented is that workers in an organization do not voluntarily accept the proper use of safety glasses (PPE). This paper attempts to define the relationship between the quality of PPE, self-care, working conditions and the type of work performed by the workers and the levels of acceptance of the proper use of PPE. The validity and reliability of the instruments “PPE evaluation data sheet” and “technical survey”, applied to workers, were determined by Cronbach’s alpha test, which yielded a coefficient (α > 0.75) for both instruments. The results of the hypothesis tests (X2 < 0.05) show a significant relationship between the quality of PPE and self-care and the levels of acceptance of the proper use of PPE, with a greater significance with respect to working conditions and the type of work performed (diamond drilling), due to the compatibility of use and ergonomic design of PPE.